Usability of Marble Waste as a Road Base Material, Case Study of Bilecik Province - Ahmet Neim Kahveci; Nazile Ural (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
As a result of the constantly increasing needs, developments in technology and industry cause an increase in waste. With the increase of wastes, it has become necessary to recycle wastes in order to reduce the environmental problems that arise. For this purpose, many sectors try to minimize the expenses during the manufacturing stages, energy consumption, raw material, and space usage as much as possible. In the construction industry, where raw material consumption is the highest, the most consumed raw material is aggregate. Approximately 95% of the materials used in road constructions consist of aggregate, and the aggregate used is obtained from the quarries. The need for aggregate quarries is increasing day by day and the general structure of the earth is partially deformed. In this context, the wastes generated in the marble quarries of Bilecik province were evaluated as road base material according to the Turkey Highways Technical Specification (TKTŞ). Laboratory experiments defined in TKTŞ were carried out and the results showed that marble wastes can be used as road base material. As a result, using marble wastes as road base material will provide an environmental and economic benefit.